Karakteristik Budidaya Kakao (Theobroma Cacao L.) Pada Perkebunan Rakyat Di Kecamatan Timpeh Kabupaten Dharmasraya - Leslie Selviana Purba; Yulistriani; Wulan Kumala Sari (Jurusan Budidaya Perkebunan, 2021)
Cacao (Theobroma cacao L.) is a plantation commodity that has high economic value. The characteristics of cacao cultivation are used to describe the cultivation method or technique in a cacao plantation. The objective of this study was to collect data about the characteristics of cultivation in the smallholder cacao plantations in Timpeh Sub-district, Dharmasraya District. This research was carried out from January until March 2021 located in Timpeh Sub-district, Dharmasraya District, specific in Panyubarangan, Tabek, Timpeh and Ranah Palabi Village. This research was a survey by interviews the cacao farmers, followed by collecting data directly to the field by purposive sampling method with the criteria of respondents who having cacao farm of > 0.25 ha. The data collected were the characteristics of cacao cultivation techniques, i.e. planting material aspects (type of planting material/clone and its origin), land preparation aspects (planting spacing, planting holes and shade plants), maintenance aspects (fertilization, pruning and sanitation), aspects of pest and disease control (types of pests and diseases that attack and types of control) and harvest aspects. The obtained data were analized and shown descriptively. The results showed that the respondents (cacao farmers) in Timpeh Sub-district, Dharmasraya District had not carried out the optimal cacao cultivation techniques as indicated by the low cacao production there (50-200 kg/ha/year).